Host preference and mortality caused by the parasitoid Sclerodermus guani on different cerambycid species - Qun Yu; Shuang Li; Yu-Jun Kong; Zuo-Xiang Sun; Dan-Dan Cao; Jian-Rong Wei (BioControl, 2024)

Assessment of Beauveria bassiana for the biological control of corn borer, Ostrinia furnacalis, in sweet maize by irrigation application - Mengxia Feng; Yunyue Zhang; Brad Steven Coates; Qian Du; Yuebo Gao; Lili Li; Haibin Yuan; Wei Sun; Xue Chang; Shuxiang Zhou; Yangzhou Wang (BioControl, 2023)
Kernels of sweet maize are directly consumed by humans. This high value crop is grown in arid and semi-arid regions of western Jilin Province, China where trickle irrigation is widely used and larvae of the corn borer, Ostrinia furnacalis Guenée (Lepidoptera: Crambidae), can cause significant kernel damage. Low humidity in arid regions is less conducive to the efficacy of the biological control agent, Beauveria bassiana (Balsamo) Vuillemin (Hypocreales: Cordycipitaceae). Simulated semi-arid conditions in greenhouse experiments were conducted comparing B. bassiana application on a granule carrier or in aqueous suspension to sweet maize. Applications of B. bassiana adhered to granules and in suspension reduced O. furnacalis leaf feeding damage, number of boreholes and tunneling length. Treatments with a granular carrier showed the most significant reductions in maize damage when applied once at whorl stage and in combination with a second application at the ear. The greatest reductions in boring and tunneling attributed to these treatments occurred at internodes around the ear. Although reduced damage was greatest following granular compared to aqueous applications, the latter also provided significant reductions in feeding damage compared to controls. This study demonstrates the utility of B. bassiana as a biological control agent for the reduction in damage caused by second-generation corn borer to sweet maize and existing irrigation equipment could be adapted for efficacious aqueous treatments by growers.

Host adaptation of a gregarious parasitoid Sclerodermus harmandi in artificial rearing - Li Li; Wei Wei; Zhudong Liu; Jianghua Sun (BioControl, 2010)